Pengaruh Revolusi Industri Terhadap Perkembangan Desain Modern - Yunida Sofiana (Humaniora, 2014)
The Industrial revolution of the second half of the eighteenth century in Britain was the beginning era of the design modern. Pros and Cons from these revolution happens to comes up with a new movement to art and design that called Art and Craft Movement and Art Nouveau that will be given a tremendous impacts on design modern. Different design approach will be contributed on developing design modern. The research method that has been used for this paper was desk-research method by collected secondary data and analyses to find conclusion about how did the industrial revolution contributed to modern design. The beauty of a design derived from the expertise in exploring new material and technology. The lack in artistic and decorative aspects set new structural and functional display of a design.